MENINGKATKAN MEMBACA PEMAHAMAN BAHASA ARAB SISWA MELALUI MODEL KOOPERATIF TIPE CIRC DI MAN PADANG PANJANG - SUHARMON SUHARMON (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2011)
his research aimed improving students’ reading comprehension in Arabic by using Cooperative Integrated Reading and Composition (CIRC) at MAN 3 Padangpanjang. To reach the aim, qualitative approach and classroom action research (CAR) were used. The participants of the research were students of grade XI/2 MAN 3 Padangpanjang. The research was conducted during July-August in 2008/2009 academic year which consisted 3 cycles. The data were collected employing such techniques as of test, observation, interview and in depth discussion among the researcher team, peer and collaborator for the reflection and supported by the following tools as reading comprehension test, observation sheet, interview guidance, questionnaire and discussion sheet. The finding showed that CIRC improved students reading comprehension in Arabic, and learning process activity. CIRC also made reading comprehension in Arabic more enjoyable and minimize learning boredom.Kata kunci: membaca pemahaman, model pembelajaran, kooperatif tipe CIRC (Cooperative Integrated Reading and Composition).